Mass transfer intensification by microinterface: Efficient dehydration of glycerol into acrolein in a water/oil pickering emulsion system. (1st November 2019) - Zhang, Jiaojiao; Li, Zheng; Cui, Xiaojing; Li, Jinlong; Jia, Shiyu; Wang, Yingxiong; Wang, Hongliang; Hou, Xianglin; Deng, Tiansheng
Abstract: Chemical reactions with products of high reactivity generally suffer from low yields due to the severe side reactions. This is the case for the synthesis of acrolein from glycerol dehydration. To improve the yield of acrolein, fast removal of high reactive acrolein molecules from the reaction system is desirable but remains a major challenge, due to the high viscosity of glycerol. To tackle this problem, the Pickering emulsion was chosen as the reaction system in this work to accelerate the removal of acrolein. A water-in-oil Pickering emulsion was fabricated for the liquid phase dehydration of glycerol to acrolein, which exhibits twice yield of acrolein compared with the homogeneous system. The combination of the transfer experiments and IR analysis confirmed the drastic restrain of the side reactions between acrolein and glycerol, due to the intensified mass transfer of acrolein from the liquid phase by the larger microinterface of emulsion. Furthermore, the transfer rate of acrolein through the water-oil interface can be tuned via a shift in the interfacial properties of the silica emulsifier by silylation treatment. The highest acrolein yield of nearly 50% was obtained with the highest transfer rate of acrolein on the silica silylated by (MeO)3 Si(CH2 )11 CH3 . Graphical abstract: Dehydration of the glycerol to acrolein in emulsion was improved with mass transfer intensification by microinterface of Pickering emulsion, in which the acrolein yield reached twice time as compared with that in homogeneous reaction system. Image 1 Highlights: Dehydration of glycerol to acrolein in a Pickering emulsion provides twice yield compared with the homogeneous system. The higher yield originates from the intensified transfer of acrolein by the vast microinterface of Pickering emulsion. A positive correlation can be established between acrolein yield and its transfer rate through the oil-water interface.